2022
DOI: 10.3389/fbioe.2021.792489
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nucleic Acid Frameworks in the Construction of Nanostructures and Cascade Biocatalysts: Recent Progress and Perspective

Abstract: Nucleic acids underlie the storage and retrieval of genetic information literally in all living organisms, and also provide us excellent materials for making artificial nanostructures and scaffolds for constructing multi-enzyme systems with outstanding performance in catalyzing various cascade reactions, due to their highly diverse and yet controllable structures, which are well determined by their sequences. The introduction of unnatural moieties into nucleic acids dramatically increased the diversity of sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 216 publications
0
17
0
Order By: Relevance
“…Although only one atom or group in the pentose is substituted, some of these modifications lead to significant changes of the properties of DNA or RNA. For example, 2'-F and 2'-OMe modifications greatly increase the melting temperatures, the duplex stabilities, and nuclease resistances of the nucleic acids 45 . Replacement of the oxygen in the sugar ring with sulfur leads to the production of 4'-thiol-modified DNA and RNA, which have been prepared and investigated by Matsuda and co-workers 46,47 .…”
Section: Unnatural Nucleic Acids With Altered Sugar Backbonementioning
confidence: 99%
See 3 more Smart Citations
“…Although only one atom or group in the pentose is substituted, some of these modifications lead to significant changes of the properties of DNA or RNA. For example, 2'-F and 2'-OMe modifications greatly increase the melting temperatures, the duplex stabilities, and nuclease resistances of the nucleic acids 45 . Replacement of the oxygen in the sugar ring with sulfur leads to the production of 4'-thiol-modified DNA and RNA, which have been prepared and investigated by Matsuda and co-workers 46,47 .…”
Section: Unnatural Nucleic Acids With Altered Sugar Backbonementioning
confidence: 99%
“…For example, 2 0 -F and 2 0 -OMe modifications greatly increase the melting temperatures, the duplex stabilities, and nuclease resistances of the nucleic acids. 45 Replacement of the oxygen in the sugar ring with sulfur leads to the production of 4 0 -thiol-modified DNA and RNA, which have been prepared and investigated by Matsuda and co-workers. 46,47 They demonstrated that 4 0 -thiol-modified RNA can be transcribed from a DNA template with 4 0 -thiol-CTP and 4 0 -thiol-UTP by T7 RNAP, and 4 0 -thiol-modified DNA can be efficiently amplified by KOD dash DNAP under appropriate conditions and transcribed by T7 RNAP in vitro and by mammalian RNA polymerases in mammalian cells.…”
Section: Unnatural Base Pairs (Ubps)mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the high surface area volume ratio, compatible capture and release ability, nanomaterials provide a high collision probability for antibodies and CTCs ( Park et al, 2017 ; Wu C. et al, 2019 ; Shi et al, 2022 ; Yi et al, 2022 ; Liu et al, 2022 ; Liu J. et al, 2021 ), which can help improve the sensitivity and specificity of capture, and have attracted extensive attention in the separation of CTCs ( Wongkaew et al, 2018 ; Wu and Qu, 2015 ; Zhu G. et al, 2021 ; Naskar et al, 2020 ; Chandankere et al, 2020 ). So far, carbon nanotubes (CNTs) ( Cho H. et al, 2018 ; Zhang P. et al, 2019 ; Poudineh et al, 2017 ), graphene oxide (GO) ( Chen et al, 2012 ; Yoon et al, 2013 ; Yu X. et al, 2013 ; Yoon et al, 2016 ), gold nanoparticles (AuNP) ( Park et al, 2017 ), nanocolumns ( Lin et al, 2014 ; Shi et al, 2022 ) and TiO 2 nanofibers ( Zhang et al, 2012 ) have been widely used in affinity group capture methods ( Zhao et al, 2016 ; Cai et al, 2017 ; Wongkaew et al, 2018 ).…”
Section: Microfluidic Technologies For Ctcs Separationmentioning
confidence: 99%